Conquering lignin recalcitrance by Pandoraea sp. B-6 to improve co-solvent pretreatment of corn stover. (December 2018) - Zhuo, Shengnan; Peng, Bing; Yan, Xu; Zhang, Kejing; Si, Mengying; Liu, Mingren; Shi, Yan
Graphical abstract: Highlights: A pretreatment strategy using bacteria-assisted THF–H2O co-solvent (THCB) was proposed. Lignin was removed to a low content of 3.7% by THCB pretreatment. A maximum reducing sugar yield of 827.2 mg/g was released from corn stover after THCB pretreatment. The THCB pretreatment method for lignocellulosic biomass we provided is energy-saving strategy. Abstract: Chemical pretreatments significantly improve the enzymatic hydrolysis of lignocellulosic biomass, however, lignin, more or less, left in the residue still presents a significant challenge for the sugar yield. To address this challenge, we proposed a pretreatment strategy using bacteria-assisted (tetrahydrofuran) THF–H2 O co-solvent (THCB) to enhance enzymatic hydrolysis under mild conditions. Pandoraea sp. B-6 was proved to effectively remove lignin (to 3.7%) in the corn stover (CS) residue after THF–H2 O co-solvent (THC) pretreatment. The compositional and structural analysis confirmed that lignin removal contributed to the expose of more cellulose. The sugar yield varied from 129.6 mg/g to 827.2 mg/g after THCB pretreatment under different conditions, which was increased by 42.6%∼2.8% over THC pretreatment (90.8 mg/g∼804.5 mg/g) and 1.5∼9.7 times over the untreated CS (84.8 mg/g). Our founding provides a promising technology for lignocellulosic biomass pretreatment in terms of advanced lignin removal, enzymatic digestibility, and reduced energy consumption.